2015
DOI: 10.1371/journal.pone.0129931
|View full text |Cite
|
Sign up to set email alerts
|

Differential Epigenetic Effects of Atmospheric Cold Plasma on MCF-7 and MDA-MB-231 Breast Cancer Cells

Abstract: Cold atmospheric plasma (plasma) has emerged as a novel tool for a cancer treatment option, having been successfully applied to a few types of cancer cells, as well as tissues. However, to date, no studies have been performed to examine the effect of plasma on epigenetic alterations, including CpG methylation. In this study, the effects of plasma on DNA methylation changes in breast cancer cells were examined by treating cultured MCF-7 and MDA-MB-231 cells, representing estrogen-positive and estrogen-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…Using MCF7 and MDAMB231 as the modeling cell lines, Sung‐Bin Park et al reported that MDAMB231 cells are more sensitive to PAM than MCF7 cells, which is consistent with our findings that TN breast cancer cells are more responsive to PAM and have unique treatment profiles. Currently, three hypotheses could be used to explain such a phenomena.…”
Section: Discussionsupporting
confidence: 92%
“…Using MCF7 and MDAMB231 as the modeling cell lines, Sung‐Bin Park et al reported that MDAMB231 cells are more sensitive to PAM than MCF7 cells, which is consistent with our findings that TN breast cancer cells are more responsive to PAM and have unique treatment profiles. Currently, three hypotheses could be used to explain such a phenomena.…”
Section: Discussionsupporting
confidence: 92%
“…Results of current studies show that NTP can induce apoptosis in vitro in various cancer types, from lung cancer, glioblastoma, prostate cancer, melanoma and cervical cancer to breast cancer 12 17 . Previous studies suggest that RONS generated by NTP plays an important role in cell death.…”
Section: Introductionmentioning
confidence: 79%
“…This discovery was reported in vitro and in vivo for different non-thermal plasmas, where studies were conducted on a variety of cancer types 6 including melanoma 7 , cervical cancer 8 , hepatocellular carcinoma, breast carcinoma 9 , papilloma, colon cancer, glioblastoma, etc. 6 .…”
Section: Introductionmentioning
confidence: 89%